Body Composition Adjusted Dosing of Gemcitabine-Nab-Paclitaxel in Pancreatic Cancer Does Not Predict Toxicity Compared to Body Surface Area Dosing. (19th May 2019) - Freckelton, Julia; Croagh, Daniel; Holt, Darcy Quinn; Fox, Adrian; Wong, Rachel; Lee, Margaret; Moore, Gregory Thomas
Abstract: Combination gemcitabine and nab-paclitaxel (Gem-Nab-P) is a common regimen used to treat metastatic pancreatic ductal adenocarcinoma (PDAC). Toxicity from this regimen is associated with significant morbidity. Currently, Gem-Nab-P is dosed using estimated body surface area, derived from height and weight. This study investigates whether skeletal muscle assessment could be a useful tool in the dosing of Gem-Nab-P in metastatic PDAC. This study included 52 patients who had received first-line treatment with Gem-Nab-P for PDAC. Demographic and chemotherapy treatment information was gathered from medical records and body composition analysis was performed using single slice computed tomography methods, at spinal level L3. Patients who experienced first-cycle chemotherapy-associated toxicity did not have a different median skeletal muscle area (SkMA) to those who did not (128.6 cm 2 vs. 111.4 cm 2, P  =   0.2). There was also no difference in the gemcitabine dose to SkMA ratio (14.1 mg/cm 2 vs. 14.4 mg/cm 2, P  = 0.8), nab-paclitaxel to SkMA ratio (1.8 mg/cm 2 vs. 1.8 mg/cm 2, P  = 0.6) or combined dose equivalent to SkMA ratio (2.8 mg/cm 2 vs. 2.9 mg/cm 2, P  = 0.9) between the patients that experienced first cycle toxicity versus those that did not. This study suggests that a PDAC patient's SkMA is unlikely to be a useful addition to conventional body surface area in the dosing of first-line Gem-Nab-P, to reduce first-cycle toxicity.